Sebum‐Membrane‐Inspired Protein‐Based Bioprotonic Hydrogel for Artificial Skin and Human‐Machine Merging Interface. (22nd January 2023) - Leng, Ziwei; Zhu, Pengcheng; Wang, Xiangcheng; Wang, Yifan; Li, Peishuo; Huang, Wei; Li, Bingchen; Jin, Rui; Han, Ningning; Wu, Jing; Mao, Yanchao
Abstract: As an on‐skin electronic device, artificial skin shows great potential in medical monitoring and personal electronics, which also holds promise to develop human‐machine merging interfaces. However, merging artificial skins with human bodies is largely restricted by the dissimilarity of material compositions in existing artificial skins and biological tissues. Naturally conductive protein is a potential material candidate for artificial skins, nevertheless, it suffers from the critical issue of dehydration which harms its proton conductivity. Inspired by the sebum membrane of human skin, herein,  a protein‐based bioprotonic hydrogel (PBH) with reliable water retention ability is reported for artificial skins. The bovine serum albumin with natural proton conductivity is utilized in the PBH, and the glycerol that originally presents on human skin surface is used as an artificial sebum membrane to retain water. The PBH can act as a bioprotonic skin (B‐skin) for collecting electrophysiological signals and self‐powered sensing. Based on the B‐skin, intelligent robot and cellphone control systems are demonstrated. Compared with present artificial skins, this B‐skin is all made out of biological materials that are consistent with material components of human skin tissues including proteins, endogenous glycerol, and water. Such a B‐skin may enable the development of next‐generation human‐machine merging interfaces. Abstract : A protein‐based bioprotonic hydrogel (PBH) with reliable water retention ability is developed for artificial skins. The PBH can act as a bioprotonic skin (B‐skin) to collect high‐quality human electrophysiological signals for a long time. Based on the B‐skin, intelligent robot and cellphone control systems are further demonstrated. This B‐skin offers great potential to develop next‐generation human‐machine merging interfaces.